Pembentukan Gaharu Gyrinops versteegii oleh Bioinduksi Fusarium solani dengan Teknik Simpori - Resti Wahyuni; Amalia Indah Prihantini; Lutfi Anggadhania (Jurnal Ilmu Pertanian Indonesia, 2020)
Agarwood is a non-timber forest product having high economic value. However, its population in nature is getting decrease. An effort to reduce the agarwood hunting in the nature is agarwood cultivation. One of agarwood inoculation methods is simpori as a modification of inoculation method using Fusarium solani and porous nails. The present study aimed to determine the effect of F. solani dosage to the quantity and quality of Gyrinops versteegii agarwood using simpori. The simpori technique used completely randomized design with 3 treatments and 10 replications. The treatments were F. solani at a dosage of 3 mL/porous nail (P0), F. solani at a dosage of 9 mL/porous nail (P1), and F. solani at a dosage of 6 mL/porous nail (P2). The result showed that both dimensions of agarwood formation and the agarwood produced at 7 months after the first inoculation in all treatments were not significant. The highest length and the highest depth of agarwood formation were shown by P1 (5.1 cm) and P0 (7 cm) treatments, respectively. The highest agarwood production was observed in P1 and P2 treatments (0.032%). The visual quality of agarwood based on SNI 7631:2011 equal to kemedangan TG.C. The agarwood quality based on sesquiterpenes and chromone derivatives contents was different in all treatments. P2 treatment showed the highest content of sesquiterpenes and chromone derivatives (17.5%). The difference of F. solani dosages produce agarwood with the same quantity but different in quality when harvest 7 month after the first inoculation. Keywords: agarwood, phenylethyl chromone derivatives, sesquiterpenes, simpori